TINGKAT PREVALENSI DAN FAKTOR-FAKTOR DETERMINA N KESEJAHTERAAN KELUARGA DI KABUPATEN LEMBATA, NTT (Bagian dari Tesis) - Hasan Ibrahim (Politeknik Pertanian Negeri Kupang, 2009)
The quality life of a family is describing the level of welfare. The better the family quality, the higher the level of welfare. This research was conducted in Sub districts of Nubatukan and Ille Ape, Lembata Regency, East Nusa Tenggara Timur. The objectives of this research were: to measure the prevalence level of poor family and to analyze the factors which related with family welfare level. A hundred families are used as sample which is chosen by purposive random sampling and stratified random sampling method. On the studied location,Â the variety of poverty prevalency depend on the indicator used, which, 66% (BPS Indicators), 78% (BKKN Indicators), and 31% (subjective indicators). Factors which are significantly (p<0.05) related with welfare is sex. Level of education, and profetion (job)Â of family leader. Key words: Welfare, Poverty, Prevalence.